Lipid-lowering drug and complement factor H genotyping–personalized treatment strategy for age-related macular degeneration - Can Can Xue; Kelvin Y.C. Teo; Yih Chung Tham; Hengtong Li; Sahil Thakur; Charumathi Sabanayagam; Qiao Fan; David L. Silver; Xiaomeng Wang; Chui Ming Gemmy Cheung; Tien Yin Wong; Usha Chakravarthy; et al. (iScience, 2024)
Summary: We investigated whether the effect of lipid-lowering drugs (LLDs) on age-related macular degeneration (AMD) differs according to the main complement genetic variants in Singapore Epidemiology of Eye Diseases (SEED) (n = 5,579) and UK Biobank studies (n = 445,727). The effect of LLD was determined for each stratum of 20 complement genetic variants. In SEED, 484 individuals developed AMD and 216 showed progression over 6 years. In the UK Biobank, 913 participants developed AMD over 11 years. rs1061170 variant (complement factor H gene) was the only variant for which we found a protective effect in both populations. This effect was found in individuals carrying at least one C allele in SEED (odds ratio [OR] = 0.41; 95% confidence interval [CI], 0.19–0.87) and in individuals carrying two C alleles in UK Biobank (hazard ratio [HR] = 0.65; 95% CI, 0.45–0.93). These effects corresponded to a 50% and 35% decrease in AMD risk, respectively. Our study highlights the potential for personalized therapy for AMD based on complement genotyping.